2021
DOI: 10.1002/clt2.12044
|View full text |Cite
|
Sign up to set email alerts
|

Patients with suspected allergic reactions to COVID‐19 vaccines can be safely revaccinated after diagnostic work‐up

Abstract: Background: When initiating the Danish vaccination program against COVID-19, the incidence of anaphylaxis was estimated to be 10 times higher compared to other virus-based vaccines. In this study, we present data on patients referred with suspected allergic reactions to COVID-19 vaccines. The main purpose of the study is to investigate the incidence and severity of the allergic reactions, and to evaluate the safety of revaccination. Methods: All patients in the region of Southern Denmark with case histories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 18 publications
6
51
0
Order By: Relevance
“… 136 An allergological work‐up for patients with a possible risk of severe hypersensitivity reactions is recommended. 137 The patients should be evaluated with skin tests for the vaccine and its excipients. Alternative vaccines that do not contain the suspected components could be considered in case of a positive skin result.…”
Section: Vaccination Of Covid‐19 and Allergymentioning
confidence: 99%
“… 136 An allergological work‐up for patients with a possible risk of severe hypersensitivity reactions is recommended. 137 The patients should be evaluated with skin tests for the vaccine and its excipients. Alternative vaccines that do not contain the suspected components could be considered in case of a positive skin result.…”
Section: Vaccination Of Covid‐19 and Allergymentioning
confidence: 99%
“… 6 During the COVID‐19 epidemic focus has been on these two excipients as they are excipients in the first vaccines on the market in Europe and possible culprits for allergic reactions to the COVID‐19 vaccines. 7 , 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…We have recently published results on anaphylactic reactions to COVID‐19 vaccines in the normal population and found the incidence to be similar to other virus‐based vaccines. 10 Of 55 patients with reactions to the first dose 52 patients were re‐vaccinated without adverse reactions. Three patients were diagnosed with allergy to drug excipients.…”
Section: Introductionmentioning
confidence: 99%
“…However, after investigation, true allergy is rarely found and many are not IgE mediated 1 and are often labelled immunogenic reactions. Recent studies have shown successful revaccination in patients who had suspected allergic reactions to their first dose 2,3 . Polysorbate 80 (PS80) is the potentially allergenic excipient in the AstraZeneca and Janssen/Johnson and Johnson COVID‐19 vaccines.…”
Section: Introductionmentioning
confidence: 99%